"My Teacher Doesn't Like Me": Perceptions of Teacher Discrimination and School Discipline among African-American and Caribbean Black Adolescent Girls - Sheretta T. Butler-Barnes; Misha N. Inniss-Thompson (MDPI AG, 2020)
This study examined the impact of perceived teacher discrimination on the school discipline of African-American and Caribbean Black adolescent girls. The findings are drawn from a nationally representative sample of (n = 410) African-American and (n = 193) Caribbean Black adolescent girls age 13 to 17 (Mage = 15). Results indicate that perceiving discrimination from teachers was associated with higher school discipline (e.g., suspension, expulsion, and spending time in a jail, detention center) for African-American girls. For Caribbean Black girls, higher household income and school bonding was associated with lower school discipline. Older Caribbean Black girls were also more likely to receive higher school discipline. However, perceiving discrimination from teachers was not associated with school discipline for Caribbean Black girls. The developmental significance and implications for future research are discussed.